2017
DOI: 10.1182/blood-2016-12-758995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a near-universal hospitalization-based prophylaxis regimen on annual number of venous thromboembolism events in the US

Abstract: • Approximately 500 000 US VTE events occur annually; approximately one-half are related to current or recent hospitalization.• VTE attack rates (2005)(2006)(2007)(2008)(2009)(2010) did not change despite nearuniversal in-hospital VTE prophylaxis, possibly due to short prophylaxis duration.The annual number of US venous thromboembolism (VTE) events, the number of potentially preventable events, and the effect of hospitalization-based prophylaxis are uncertain. We estimated VTE attack (incident plus recurrent V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 33 publications
2
87
0
3
Order By: Relevance
“…The 30-day mortality rate observed in this study is lower than the 30-day mortality rate of 50% observed among patients who were receiving warfarin and presented with intracranial hemorrhage and than the 30-day mortality rate of 30% observed among patients who were receiving warfarin and were about to undergo emergency intervention. [12][13][14][15][16][17] However, it is similar to the 30-day mortality rate of 15% observed among the first 67 patients enrolled in a study of andexanet for the reversal of factor Xa inhibitors in patients with serious bleeding. 18 The rate of thrombotic events was 4.8% at 30 days and 6.8% at 90 days, and the 30-day rate was similar in group A and group B (5.0% and 4.6%, respectively).…”
Section: Discussionmentioning
confidence: 63%
“…The 30-day mortality rate observed in this study is lower than the 30-day mortality rate of 50% observed among patients who were receiving warfarin and presented with intracranial hemorrhage and than the 30-day mortality rate of 30% observed among patients who were receiving warfarin and were about to undergo emergency intervention. [12][13][14][15][16][17] However, it is similar to the 30-day mortality rate of 15% observed among the first 67 patients enrolled in a study of andexanet for the reversal of factor Xa inhibitors in patients with serious bleeding. 18 The rate of thrombotic events was 4.8% at 30 days and 6.8% at 90 days, and the 30-day rate was similar in group A and group B (5.0% and 4.6%, respectively).…”
Section: Discussionmentioning
confidence: 63%
“…For instance, guidelines now suggest extended or lifelong duration of anticoagulant therapy in men with a first unprovoked event, while previously, a limited treatment duration was recommended for these patients . Pulmonary embolism is now almost always diagnosed with computed tomography (CT) angiography or ventilation perfusion scan instead of (the gold standard) pulmonary angiography, and for several risk situations, such as surgery, near‐universal thromboprophylaxis strategies have been implemented . In addition, the prevalence of risk factors for venous thrombosis in populations is continuously changing.…”
Section: Introductionmentioning
confidence: 99%
“…Most VTE events (67%) occurred within 30 days of discharge; 20% of events occurred between 1 and 2 months, and 13% occurred between months 2 and 3 . A similar review among Olmsted County residents in Minnesota demonstrated that 75% of VTE events occurred after discharge, with a median time of 19.5 days . Data further supporting the risk of VTE beyond hospitalization come from an international registry of more than 11,000 patients that demonstrated the highest incidence of VTE occurred in the first 30 days after discharge (38%) …”
Section: Venous Thromboembolism Inpatient Risk Assessment Model Per Amentioning
confidence: 93%
“…In the major trials supporting VTE prophylaxis in medically ill patients, the duration of prophylaxis was 6–14 days . Today, acutely ill medical patients are typically hospitalized for 3–5 days and do not routinely receive prophylaxis after discharge . Several observational trials demonstrated that risk of VTE extends beyond hospitalization .…”
Section: Venous Thromboembolism Inpatient Risk Assessment Model Per Amentioning
confidence: 99%